Thermodynamics and kinetics of gaseous metal hydroxide formation from oxides relevant to power and propulsion applications. (December 2016) - Opila, E.J.
Abstract: The thermodynamics and kinetics of gaseous metal hydroxide formation from simple oxides important for power and propulsion applications are reviewed. The transpiration technique for determining thermodynamics of gaseous metal hydroxide is highlighted. The status of thermodynamic data for CrO2 (OH)2 (g), Si(OH)4 (g), and Al(OH)3 (g) in available databases is described. A thermodynamic argument is presented for the trend that gaseous metal hydroxides with more –OH groups will have a greater pressure dependence and a lower temperature dependence of reaction from their condensed phase oxide than those gaseous metal hydroxides with few –OH groups. Finally, the need for thermodynamic data for Ti-, Mn-, Y-, and Ta-gaseous metal hydroxides is summarized.